Pengaruh Persepsi Kemudahan Dan Fitur Layanan Terhadap Minat Peserta Menggunakan Aplikasi Mobile JKN - Dewi Wijiastuti, Retno; Nur Fadhilah Febriyanti, Eka (EkoPreneur, 2024)
This study aims to analyze the influence of perceived convenience and service features on participants' interest in using the Mobile JKN application among BPJS Kesehatan participants at Puskesmas Sorong. Employing a quantitative approach with a causal method, the research involved 120 respondents selected through purposive sampling. Data were collected via questionnaires and analyzed using multiple linear regression with SPSS version 20. The findings reveal that perceived convenience significantly influences participants' interest in using the Mobile JKN application, with a t-value of 9.426 > t-table 1.980 and a significance value of 0.000. Service features also have a significant positive effect, with a t-value of 9.838 > t-table 1.980 and a significance value of 0.000. Simultaneously, perceived convenience and service features jointly influence interest, with an F-value of 65.535 > F-table 3.07 and a significance value of 0.000. The coefficient of determination (R²) indicates that 52.8% of the variance in participants' interest can be explained by perceived convenience and service features, while 47.2% is influenced by other factors. The study emphasizes the critical role of user-friendly digital health applications with comprehensive service features in increasing adoption rates. The findings suggest that developers should design more intuitive and responsive features to meet user needs. The research is limited to the Sorong region, which may affect the generalizability of the results. Future studies should consider expanding the geographical scope for more representative findings.